Panel Data Regression Modeling of North Sumatra Province's Gross Regional Domestic Product for 2019-2023 - Maylani, Ester; Sari, Rina Filia (Universitas Islam Lamongan, 2025)
Regional economic growth is influenced by various factors that need to be analyzed accurately to support the formulation of effective policies. This study aims to analyze the influence of economic factors on the Gross Regional Domestic Product (GRDP) in North Sumatra Province. The main issue raised is the need for an appropriate model to understand the relationship between economic variables and GRDP. This study uses panel data from 33 districts/cities during the period 2019–2023 obtained from official sources. Through Chow, Hausman, and Lagrange Multiplier tests, the Fixed Effect model was selected. The results indicate that population size, number of poor people, and Human Development Index (HDI) significantly influence RDP.